2017
DOI: 10.1177/1040638717743280
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Ki67 and its correlation with mitotic index in dogs with diffuse large B-cell lymphoma treated with 19-week CHOP-based protocol

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common type of lymphoma in dogs. We evaluated Ki67 immunoexpression and mitotic index (MI) in dogs diagnosed with DLBCL and treated with a 19-wk CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) protocol. Twenty-nine lymph node samples from dogs diagnosed with DLBCL were analyzed for Ki67 immunostaining, and positive cells present in 1 cm were counted in a grid reticle for comparison of survival times above and below the means. The Ki67 mean was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 19 publications
3
30
2
Order By: Relevance
“…Remission time ranged from 84 to 126 days, and the overall survival time varied from 167 to 244 days [11]. Similar differences in response to treatment using different protocols containing TOPIIa inhibitors in relation to various subtypes of B-cell and T-cell lymphomas have been demonstrated in other studies [12,21,26,27,49]. Our study revealed that both B-cell and T-cell lymphoma group showed differentiated TOPIIa expression.…”
Section: Discussionsupporting
confidence: 84%
“…Remission time ranged from 84 to 126 days, and the overall survival time varied from 167 to 244 days [11]. Similar differences in response to treatment using different protocols containing TOPIIa inhibitors in relation to various subtypes of B-cell and T-cell lymphomas have been demonstrated in other studies [12,21,26,27,49]. Our study revealed that both B-cell and T-cell lymphoma group showed differentiated TOPIIa expression.…”
Section: Discussionsupporting
confidence: 84%
“…To the authors' knowledge, there are also many published reports regarding prognosis of canine lymphoma 8‐14 . Based on this literature, we supported the hypothesis that it may be possible to choose an optimal first‐line treatment for dogs with localized SIL by identifying therapeutic biomarkers influencing the success of chemotherapy or surgery from numerous prognoses or predictive factors in the published data 8‐14 …”
Section: Introductionsupporting
confidence: 69%
“…There are several human publications regarding biomarkers or determinants for treatment success in some types of lymphoma, and most of these researchers discussed that the presence of these factors might affect treatment response and outcomes 2,7 . To the authors' knowledge, there are also many published reports regarding prognosis of canine lymphoma 8‐14 . Based on this literature, we supported the hypothesis that it may be possible to choose an optimal first‐line treatment for dogs with localized SIL by identifying therapeutic biomarkers influencing the success of chemotherapy or surgery from numerous prognoses or predictive factors in the published data 8‐14 …”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…A number of studies have explored methods to predict outcome in canine lymphoma including refining diagnostic staging methods using cytology and sonography to evaluate the liver and spleen [7], measurement of chemotherapy-induced neutropenia [8], assessment of the relative expression levels of BCL2 and MYC [9], the use of the modified Glasgow Prognostic Score [10]), the immunosignature at diagnosis [11], the assessment of Ki67 and its correlation with mitotic index [12] and flow cytometric characterization of S-phase fraction and ploidy in lymph node aspirates [13]. To date, no useful prognostic indicators have been established that consistently correlate with either the length or lack of remission.…”
Section: Introductionmentioning
confidence: 99%